Information and communication technology and good governance: the establishment of transparency of information and the Toward fight against corruption - naouel, Meghzili (Milev Journal of Research and Studies, 2018)
This paper attempts to highlight the relationship between information technology and communication and good governance in the light of a set of principles, namely transparency and combating corruption , As well as the answer to the problematic: What is the extent of the contribution of information and communication technology in achieving information transparency and combating corruption? In order to answer this problematic, the concepts of the study will first be defined, then an analysis of the role of information and communication technology in establishing transparency and combating corruption. Finally, we have reached the conclusion that information and communication technologies can contribute to combating corruption by applying transparency in the work of government units by providing information For everyone